GE_GERICHTE P/21832/2016 vom 20. Juli 2020 - GE Cour de justice (2020)
BLANCHIMENT D'ARGENT;PAPER TRAIL;ESCROQUERIE;PRÉTENTION FRAUDULEUSE ENVERS L'ASSUREUR;PARTIE CIVILE;CONFISCATION(DROIT PÉNAL);DOMMAGES-INTÉRÊTS | CP.305bis; CP.146; CPP.124; CPP.126; CP.70